Effect of soaking time on the removal of pericarp of green pepper berries - Hasaman, Norfarahin; Shamsudin, Rosnah; Mohd Adzahan, Noranizan; Abdul Rahman, Russly (Faculty of Engineering, Universiti Putra Malaysia, 2012)
White peppercorn is obtained from fresh pepper berries that undergo a few processes. The processes include harvesting, threshing (optional), soaking, rubbing, cleaning and drying. The most critical parts are soaking and rubbing. The current soaking method is soak the pepper berries in water for 12 – 14 days until the pericarp of the berries is rotten and the berries can be rubbed by stepping in a plastic container as used for covering food. At the same time water was pour in to dispose of the dirt and all the rotten pericarp. This method is apparently time-consuming, requires a large labour workforce and the productivity of white pepper is thus limited. In order to hasten the process, a stone disc mill is used in this study to rub the pepper berries. Different sizes of clearance of disc mill were tested to determine which one is superior and can produce a better quality of white pepper. The clearances chosen for testing were 7 mm, 6 mm and 5 mm. The samples were soaked for 4, 5 and 6 days at room temperature and tested using a stone disc mill to remove the pericarp for each day. The results show that the pericarp can be removed after the 4th day of soaking in water and the most efficient clearance is 5 mm.